1987
DOI: 10.1128/jb.169.11.4916-4922.1987
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of sulfur:ferric ion oxidoreductase from Thiobacillus ferrooxidans

Abstract: A sulfur:ferric ion oxidoreductase that utilizes ferric ion (Fe3+) as an electron acceptor of elemental sulfur was purified from iron-grown Thiobacillus ferrooxidans to an electrophoretically homogeneous state. Under anaerobic conditions in the presence of Fe3+, the enzyme reduced 4 mol of Fe3+ with 1 mol of elemental sulfur to give 4 mol of Fe2+ and 1 mol of sulfite, indicating that it corresponds to a ferric ion-reducing system (T. Sugio, C. Domatsu, O. Munakata, T. Tano, and K. Imai, Appl. Environ. Microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…Bacteria and archaea reduce elemental sulfur. W. succinogenes and Acidianus ambivalens produce quinone-dependent SR (7,41) and P. furiosus as well as Thiobacillus ferroxidans produce NAD(P)H-dependent SR (8,42). Apparently, glutathione is not required for their activity, indicating that the fungi have adapted independently from bacterial and archaeal mechanisms to reduce elemental sulfur during the course of evolution.…”
Section: Discussionmentioning
confidence: 95%
“…Bacteria and archaea reduce elemental sulfur. W. succinogenes and Acidianus ambivalens produce quinone-dependent SR (7,41) and P. furiosus as well as Thiobacillus ferroxidans produce NAD(P)H-dependent SR (8,42). Apparently, glutathione is not required for their activity, indicating that the fungi have adapted independently from bacterial and archaeal mechanisms to reduce elemental sulfur during the course of evolution.…”
Section: Discussionmentioning
confidence: 95%
“…Although the transfer of electrons from ferrous iron to oxygen has not been conclusively established, the electron transfer pathway is thought to involve two cytochromes c (Cyc2 and Cyc1), a rusticyanin, and an aa 3 -type cytochrome c oxidase. [4][5][6] On the other hand, although some enzyme activities thought to be involved in the aerobic oxidation of elemental sulfur by A. ferrooxidans were detected, [7][8][9][10][11][12][13][14][15][16] the oxidation pathway of elemental sulfur has not yet been clearly elucidated.…”
mentioning
confidence: 99%
“…Tel/Fax: +81-86-251-8306; E-mail: sugio@cc.okayama-u.ac.jp marked difference was observed in the cellular activity of an enzyme involved in the first step of sulfur oxidation in A. ferrooxidans, viz., SFORase. 12,13) A. ferrooxidans strains that showed high SFORase activity also showed high Cu-bioleaching activity. In contrast, strains that showed low SFORase activity showed low Cu-bioleaching activity.…”
Section: Isolation and Characterization Of Acidithiobacillus Ferrooximentioning
confidence: 99%
“…We have found that both iron oxidase and hydrogen sulfide:ferric ion oxidoreductase (SFORase) [12][13][14][15][16][17][18][19][20] are crucial in Cu-bioleaching by A. ferrooxidans AP19-3, 21) but when the levels of iron oxidase, SFORase, and Cu-bioleaching activities were compared among 67 strains of iron-oxidizing bacteria isolated from natural environments, no significant differences were observed in growth rates in iron medium or in the levels of cellular iron oxidase activity in the cells. However, a y To whom correspondence should be addressed.…”
Section: Isolation and Characterization Of Acidithiobacillus Ferrooximentioning
confidence: 99%